The Effect of Firm Size and Corporate Governance Structure on Corporate Social Responsibility Disclosures - Reghita Nabilla Shafira; Siti Nur Azizah; Sri Wahyuni; Hadi Pramono (Muhammadiyah Riau Accounting and Business Journal, 2021)
The purpose of this study is to empirically prove the effect of firm size and corporate governance structure (such as board of commissioner size, institutional ownership and managerial ownership) on corporate social responsibility (CSR) disclosure. The samples in this study were the mining companies listed in the Indonesia Stock Exchange in 2017-2019 using the purposive sampling method. Based on the criteria, there were 58 samples of research data. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicated that company size, institutional ownership, and managerial ownership have no effect on CSR disclosure. Meanwhile, the size of the board of commissioners has a positive effect on CSR disclosure.